Downregulation of hyperpolarization‐activated cyclic nucleotide‐gated channels (HCN) in the hippocampus of patients with medial temporal lobe epilepsy and hippocampal sclerosis (MTLE‐HS). Issue 10 (16th June 2020) - Lin, Wanrong; Qin, Jiaming; Ni, Guanzhong; Li, Yinchao; Xie, Haitao; Yu, Jiabin; Li, Hainan; Sui, Lisen; Guo, Qiang; Fang, Ziyan; Zhou, Liemin
Abstract: Changes in the expression of HCN ion channels leading to changes in I h function and neuronal excitability are considered to be possible mechanisms involved in epileptogenesis in kinds of human epilepsy. In previous animal studies of febrile seizures and temporal lobe epilepsy, changes in the expression of HCN1 and HCN2 channels at different time points and in different parts of the brain were not consistent, suggesting that transcriptional disorders involving HCNs play a crucial role in the epileptogenic process. Therefore, we aimed to assess the transcriptional regulation of HCN channels in Medial temporal lobe epilepsy with hippocampal sclerosis (MTLE‐HS) patients. This study included eight nonhippocampal sclerosis patients and 40 MTLE‐HS patients. The mRNA expression of HCN channels was evaluated by qRT‐PCR, while the protein expression was quantitatively analyzed by Western blotting. The subcellular localization of HCN channels in the hippocampus was explored by immunofluorescence. We demonstrated that the mRNA and protein expression of HCN1 and HCN2 are downregulated in controls compared to that in MTLE‐HS patients. In the hippocampal CA1/CA4 subregion and GCL, in addition to a large decrease in neurons, the expression of HCN1 and HCN2 on neuronal cell membranes was also downregulated in MTLE‐HS patients. These findings suggest that the expression of HCN channels are downregulated in MTLE‐HS, which indicates that the decline in HCN channels in the hippocampus during chronic epilepsy in MTLE‐HS patients leads to the downregulation of I h current density and function, thereby reducing the inhibitory effect and increasing neuronal excitability and eventually causing disturbances in the electrical activity of neurons.